(untitled) (International Journal of Banking and Finance, 2024)
This paper aims to determine the factors affecting cost and profit efficiency of commercial banks in Turkey and to examine the ownership effect on cost and profit efficiency in an emerging market. Another aim of the study is to carry out the most recent and longitudinal (2006-2020) analysis of efficiency in the Turkish banking industry. This study uses an intermediation approach with data envelopment analysis (DEA) as its methodology. A total of 23 commercial banks were selected as the study sample and their quarterly data from 2006- 2020 was collected. In addition, an external two-stage DEA model with Tobit regression was applied to examine the determinants of cost and profit efficiency. The results show that Turkish banks currently work with relatively higher cost efficiency than profit efficiency. On the other hand, foreign banks display a lower cost and profit efficiency performance. The downward trend in profit efficiency in the Turkish banking system sends a warning signal on the health and stability of the banking sector. Multivariate Tobit regression analysis reveals how Total Assets, Deposit Share, Asset Growth, Time Deposits, NPL, and Ownership Structure significantly affect cost and profit efficiency. Ratio of liquid assets to total assets is positively correlated with the efficiency values, in contrast to results from previous studies. Previous studies have mostly been limited to scale and technical efficiency and focused on the cost efficiency of Turkish banks. In this study, the gap in the literature is filled by a comparative examination of the cost and profit efficiency at the scale of bank ownership. The study will look at and discussed these issues at the most stable period and the pre-pandemic period in the Turkish economy.